The volatiles of pathogenic and nonpathogenic mycobacteria and related bacteria - Nawrath, Thorben; Mgode, Georgies F.; Weetjens, Bart; Kaufmann, Stefan H. E.; Schulz, Stefan (Beilstein Journal of Organic Chemistry, 2012)
Volatiles released by pathogenic and nonpathogenic mycobacteria, as well as by mycobacteria-related Nocardia spp., were analyzed. Bacteria were cultivated on solid and in liquid media, and headspace samples were collected at various times during the bacterial lifecycle to elucidate the conditions giving optimal volatile emission. Emitted volatiles were collected by using closed-loop stripping analysis (CLSA) and were analyzed by gas-chromatography–mass-spectrometry. A wide range of compounds was produced, although the absolute amount was small. Nevertheless, characteristic bouquets of compounds could be identified. Predominantly aromatic compounds and fatty-acid derivatives were released by pathogenic/nonpathogenic mycobacteria, while the two Nocardia spp. (N. asteroides and N. africana) emitted the sesquiterpene aciphyllene. Pathogenic Mycobacterium tuberculosis strains grown on agar plates produced a distinct bouquet with different volatiles, while liquid cultures produce less compounds but sometimes an earlier onset of volatile production because of their steeper growth curves under this conditions. This behavior differentiates M. tuberculosis from other mycobacteria, which generally produced fewer compounds in seemingly lower amounts. Knowledge of the production of volatiles by M. tuberculosis can facilitate the rational design of alternative and faster diagnostic measures for tuberculosis.
Keywords: aromatic compounds; CLSA; terpenes; tuberculosis; volatile profile

Advances in Microbial Physiology - Cook, G. M.; Berney, M.; Gebhard, S.; Heinemann, M.; Cox, R. A.; Danilchanka, O.; Niederweis, M. (Physiology of Mycobacteria, 2009)

Cytokines in Pulmonary Disease – Infection and Inflammation - Sangari, F. J.; Bermudez, L. E. (Marcel Dekker, Inc., 2000)

Biology of Microorganisms - Madigan, M. T.; Martinko, J. M.; Parker, J. (Prentice-Hall, 1997)

(untitled) - Wallis, R. S.; Doherty, T. M.; Onyebujoh, P.; Vahedi, M.; Laang, H.; Olesen, O.; Parida, S.; Zumla, A. (Lancet Infect. Dis., 2009)

(untitled) - Boehme, C. C.; Nabeta, P.; Hillemann, D.; Nicol, M. P.; Shenai, S.; Krapp, F.; Allen, J.; Tahirli, R.; Blakemore, R.; Rustomjee, R.; Milovic, A.; Jones, M.; et al. (N. Engl. J. Med., 2010)

(untitled) - Knechel, N. A. (Crit. Care Nurse, 2009)

(untitled) - Phillips, M.; Cataneo, R. N.; Condos, R.; Ring Erickson, G. A.; Greenberg, J.; La Bombardi, V.; Munawar, M. I.; Tietje, O. (Tuberculosis, 2007)

(untitled) - Syhre, M.; Chambers, S. T. (Tuberculosis, 2008)

(untitled) - Pavlou, A. K.; Magan, N.; Jones, J. M.; Brown, J.; Klatser, P.; Turner, A. P. F. (Biosens. Bioelectron., 2004)

(untitled) - Syhre, M.; Manning, L.; Phuanukoonnon, S.; Harino, P.; Chambers, S. T. (Tuberculosis, 2009)

(untitled) - Weetjens, B. J.; Mgode, G. F.; Machang’u, R. S.; Kazwala, R.; Mfinanga, G.; Lwilla, F.; Cox, C.; Jubitana, M.; Kanyagha, H.; Mtandu, R.; Kahwa, A.; Mwessongo, J.; et al. (Int. J. Tuberc. Lung Dis., 2009)

(untitled) - Mgode, G. F.; Weetjens, B. J.; Nawrath, T.; Cox, C.; Jubitana, M.; Machang’u, R. S.; Cohen-Bacrie, S.; Bedotto, M.; Drancourt, M.; Schulz, S.; Kaufmann, S. H. E. (J. Clin. Microbiol., 2012)

(untitled) - Konno, K. (Science, 1956)

Analysis of volatiles - Boland, W.; Ney, P.; Jaenicke, L.; Gassmann, G. A. ("closed-loop-stripping" technique as a versatile tool for metabolic studies of volatiles, 1984)

(untitled) - Dickschat, J. S.; Martens, T.; Brinkhoff, T.; Simon, M.; Schulz, S. (Chem. Biodiversity, 2005)

(untitled) - Bartelt, R. J. (Anal. Chem., 1997)

(untitled) - van den Dool, H.; Kratz, P. D. (J. Chromatogr., 1963)

(untitled) - Schulz, S.; Dickschat, J. S. (Nat. Prod. Rep., 2007)

(untitled) - Mgode, G. F.; Weetjens, B. J.; Cox, C.; Jubitana, M.; Machang’u, R. S.; Lazar, D.; Weiner, J.; van Geertruyden, J.-P.; Kaufmann, S. H. E. (Tuberculosis)

(untitled) - Prissick, F. H.; Masson, A. M. (Can. Med. Assoc. J., 1956)

(untitled) - Zur Lage, S.; Goethe, R.; Darji, A.; Valentin-Weigand, P.; Weiss, S. (Immunology, 2003)

(untitled) - Vindal, V.; Suma, K.; Ranjan, A. (BMC Genomics, 2007)

(untitled) - Gupta, A.; Bhakta, S.; Kundu, S.; Gupta, M.; Srivastava, B. S.; Srivastava, R. (J. Antimicrob. Chemother., 2009)

(untitled) - Woo, P. C. Y.; Tsoi, H.-W.; Leung, K.-W.; Lum, P. N. L.; Leung, A. S. P.; Ma, C.-H.; Kam, K.-M.; Yuen, K.-Y. (J. Clin. Microbiol., 2000)

(untitled) - Griffith, D. E.; Aksamit, T.; Brown-Elliott, B. A.; Catanzaro, A.; Daley, C.; Gordin, F.; Holland, S. M.; Horsburgh, R.; Huitt, G.; Iademarco, M. F.; Iseman, M.; Olivier, K.; et al. (Am. J. Respir. Crit. Care Med, 2007)

(untitled) - Thorel, M.-F.; Krichevsky, M.; Vincent Lévy-Frébault, V. (Int. J. Syst. Bacteriol., 1990)

(untitled) - O'Brien, M. E. R.; Saini, A.; Smith, I. E.; Webb, A.; Gregory, K.; Mendes, R.; Ryan, C.; Priest, K.; Bromelow, K. V.; Palmer, R. D.; Tuckwell, N.; Kennard, D. A.; et al. (Br. J. Cancer, 2000)

(untitled) - Blay, G.; Garcia, B.; Molina, E.; Pedro, J. R. (Tetrahedron, 2007)

(untitled) - Atmosukarto, I.; Castillo, U.; Hess, W. M.; Sears, J.; Strobel, G. (Plant Sci., 2005)

(untitled) - James, B. W.; Williams, A.; Marsh, P. D. (J. Appl. Microbiol., 2000)

(untitled) - Sorlozano, A.; Soria, I.; Roman, J.; Huertas, P.; Soto, M. J.; Piedrola, G.; Gutierrez, J. (J. Microbiol. Biotechnol., 2009)

(untitled) - Nawrath, T.; Gerth, K.; Müller, R.; Schulz, S. (ChemBioChem, 2010)

(untitled) - Nawrath, T.; Gerth, K.; Müller, R.; Schulz, S. (Chem. Biodiversity, 2010)

(untitled) - Hayaloglu, A. A.; Cakmakci, S.; Brechany, E. Y.; Deegan, K. C.; McSweeney, P. L. H. (J. Dairy Sci., 2007)

(untitled) - Callejón, R. M.; Tesfaye, W.; Torija, M. J.; Mas, A.; Troncoso, A. M.; Morales, M. L. (Food Chem., 2009)